ENVIRONMENTAL MANAGEMENT IN THE BREADMAKER MOSSORÓ-RN - Jerônimo, Carlos Enrique de Medeiros; Moura, Thiago Negreiros; Dantas, Georgia Rodrigues (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707679 In this work we performed a diagnostic environmental bakeries in the city of Mossoro, Rio Grande do Norte. The study consisted of a survey applied as objective knowledge lead to extension of technologies and practices of environmental management in the bakery segment companies. From the point of view of the objectives, it is a descriptive exploratory study, which aims to describe the problem under discussion, seeking to characterize the object of study. Following the methodology of the research was carried out a descriptive analysis of the variables of interest in the study. The data were collected through a survey on the spot, with the completion of a specific questionnaire. The results showed an improvement in the licensing procedures of the municipality, since most of the enterprises surveyed were in the process of rectification. However, best practices proactive management of water resources, solid waste, and noise and air emissions require significant improvements.